INNOVATION STRATEGY OF HEWLETT-PACKARD INDONESIA TO COMPETE IN INFORMATION TECHNOLOGY INDUSTRY - Michael Surya Gunawan; Martani Huseini (JIANA ( Jurnal Ilmu Administrasi Negara ), 2018)
Innovation Strategy of Hewlett-Packard Indonesia to Compete in InformationTechnology Industry. Research objectives : 1. Analyze the quality level of Hewlett-Packard (HP)Indonesia services provided to its customers in Indonesia, 2. Analyzing to what extent thedelegation of authority of Hewlett-Packard (HP) headquarters to Hewlett-Packard (HP) Indonesiawhich includes autonomy discretion in innovating both in terms of process and measurementinstruments (support). Knowing the information technology industry strategy in the case study isHewlett-Packard (HP) strategy in building a culture of continuous innovation that can becategorized as a strategic innovation. This study is generated through quantitative and qualitativemethod by disseminating questinaire to 112 loyal customers which have been at least 3 yearsexperience with Hewlett-Packard (HP) Indonesia as well as have spent at least 1 (one) million US$every year and interview top management of Hewlett-Packard (HP) Asia Pacific and Hewlett-Packard (HP) Indonesia. The result of research found human capital and the role of topmanagementhave played a very important role-model to implement A-to-F model in innovationand disseminate a socialization, externalization, combination and internalization (SECI) in spiralmode within company to create innovation culture. It is purposed to manage their sustainability oflife and growth in a changing strategic environment in Indonesia.